ChemInform Abstract: An Aluminophosphate Molecular Sieve with 36 Crystallographically Distinct Tetrahedral Sites. Issue 40 (30th September 2014) - Lee, Jun Kyu; Turrina, Alessandro; Zhu, Liangkui; Seo, Seungwan; Zhang, Daliang; Cox, Paul A.; Wright, Paul A.; Qiu, Shilun; Hong, Suk Bong
Abstract A new medium‐pore aluminophosphate molecular sieve, [Al72P72O288] (PST‐6), is synthesized from a mixture of NHEt2, Al2O3, P2O5 and H2O (2:1:1:40; autoclave, 200 °C, 5 d) followed by calcination under flowing air at 550 °C for 8 h.